A framework for specifying low-carbon construction materials in government procurement: A case study for concrete in a new building investment. (15th April 2022) - Jalaei, Farzad; Masoudi, Rana; Guest, Geoffrey
Abstract: There are numerous strategies that can be used to reduce the embodied carbon footprint of real property investments, many of which can be accomplished for no additional cost and with minimal performance impacts. This study aims to propose the incorporation of the life cycle carbon quantification into the government procurement of real property process in order to reach out to low-carbon durable and sustainable structures as a theoretical contribution. As a practical contribution, an integrated embodied carbon measurement application is developed in a building information model (BIM) environment to act as a decision making tool in a government office building as a case study. It supports updating procurement policies and procedures to request construction materials with lower embodied carbon in construction. Analysis of concrete assembly groups in the case study along with determination of volume of concrete in each assembly is conducted to devise a reasonable list of elements to be considered for low-carbon concrete compliancy based on an industry average benchmarking approach. Considering the numerous concrete vendors that supply concrete products to a given region, a novel concrete embodied carbon measurement approach is proposed where cradle-to-construction impacts were accounted for. The outcome of the proposed integrated tool showed the procurement of concrete mix design from one specific nearby facility resulted in more efficient GHG reductions and the results showed especially the significance of considering transportation impacts of delivering ready-mixed concrete elements to the project site. Graphical abstract: Image 1 Highlights: A material-specific embodied carbon framework into procurement is proposed. Two low-carbon material compliancy pathways are recommended. A BIM-based embodied carbon concrete calculator is developed. Procurement of concrete mix from nearby facility resulted in more efficient carbon reductions. Results showed the significance of transportation impacts to the project site.